The Reception of Fernando de Roja’s Celestina in Italy: A Polyphonic Discourse - Ferrara, Enrica Maria (Renaissance and Reformation / Renaissance et Réforme, 2017)
La Celestina by Fernando de Rojas was published in Spain for the first time in 1499 as a comedy, and as a tragicomedy in 1502. The first Italian translation of the play was published in Rome in 1506 and gave birth to a parallel and complementary textual tradition on which the reception and translation of the play in other modern languages (such as French and German) were based. Given the wide success of Celestina in Italy, this essay focuses on the hybrid genre of the play, which can be placed at the crossroads of comic and tragic genres but also on the boundaries between narrative and theatrical modes of expression. It emphasizes the importance of Celestina’s dialogic, parodic, and polyphonic structure, and its links with Dante’s Commedia and Boccaccio’s Decameron. Building on the “working hypothesis” of a Florentine genesis of Celestina, this essay explores its connection with humanist comedy and with Aretino’s comic-burlesque literature.